How To Treat and Prevention of Hypertention With Complementary Therapy In The Elderly - Dahlan, Febry Mutiariami; Aulya, Yenny (Rajaki of Tulip Medika Publisher, 2024)
Hypertension is one of the main causes of mortality and morbidity in Indonesia, so the management of this disease is a very common intervention carried out at various levels of health facilities, Hypertension is also one of the most frequent risk factors affecting the incidence of heart and blood vessel disease. The prevalence of hypertension in Indonesia continues to increase based on the Riskesdas comparison, which was around 25.8% in 2013 and increased by 34.1% in 2018. Management of hypertension is carried out as an effort to reduce the risk of rising blood pressure and its treatment. The efforts are made in the form of nonpharmacological efforts by improving health promotion and community empowerment through community-based prevention and control of hypertension. Healthy cardiac exercise besides being recommended for the elderly can also increase muscle and joint strength. The purpose of this activity is how to treat and prevention of hypertension with complementary therapy in the elderly with healthy cardiac exercise. The activity will be carried out for Elderly Women in the BPM Ermiyati, Sawangan District, Depok. The materials and tools in this community service use tools for extentions (LCD and turning sheet), Sphygmomanometer, Stethoscope, Juicer and Ingredients. This community service activity is by conducting counseling, examination, demonstration and giving star fruit juice. The stage of community service is Stages in community service; Stage of implementation of community service activities; and evaluation stage. So that, the healthy heart exercise can be given as an alternative to prevention of hypertension for elderly.